Evaluasi Keamanan Akses Jaringan Komputer Nirkabel (Kasus : Kantor Pusat Fakultas Teknik Universitas Gadjah Mada) - Ida Bagus Verry Hendrawan Manuaba; Risanuri Hidayat; Sri Suning Kusumawardani (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
The growth of current wireless networks has increased rapidly. The growth of information technology and telecommunications technology requires interoperability, joint regulation and various solutions to solve the increasingly complex problems, such as computer network security issues on wireless networks. An evaluation is needed to maintain and re-assess the stability of the network to remain adequate. This research resulted a model as a result of evaluation that can be used as a useful recommendations to improve the security of a wireless computer network access which affects the performance on the network at the Headquarters of Engineering Faculty of Gadjah Mada University.